Legal Protection of Debtors and Creditors Against Transfer of Receivables (Cessie) in The Event of Bankruptcy Related to The Principle of Justice (Universitas Negeri Semarang, 2022)
A In the current era of globalization, development is a natural thing. We can see this from the many new businesses that have sprung up. To run this business, sufficient capital is needed, one way to get this capital is through a loan to a bank by making a credit agreement and guarantee agreement. In practice, not all debtors fulfill and carry out their obligations, which results in bad loans. Therefore, the creditor in an effort to solve the problem, the creditor transfers the receivables (cessie), this is doneto reduce the risk of collateralized assets due to bad credit. This study determine the legal protection of the debtior against the transfer of receivables by cessie and to provide protection to creditors as buyers of receivable transfer. The research method used in this paper normative juridical research, namely legal research carried out by studying using library materials or secondary data with a statute approach and a conceptual approach.. Based on the results of the study, it shows that legal protection for debtors for the transfer of receivables is regulated in Article 613 and Article 1470 of the Civil Code,in the event that the Creditor partially transfers his receivables to a third party with the aim that the debtor has two unpaid debts as the fulfillment of the conditions for filing for bankruptcy, it is a misunderstanding. Because The Bankruptcy Act will lose its raison d'etre. On the other hand,in a cessie made by the creditor without notification to the debtor, then based on the provisions of Article 613 of the Civil Code, the transfer of receivables is null and void. Based on this, the authors are of the view that it is important to reformulate the Civil Code which regulates cesssie so that justice, certainty and legal benefit are realized.